2000
DOI: 10.1161/01.str.31.4.828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fixed Low-Dose Warfarin, Aspirin-Warfarin Combination Therapy, and Dose-Adjusted Warfarin on Thrombogenesis in Chronic Atrial Fibrillation

Abstract: Background and Purpose-Recent clinical trials have established that adjusted-dose warfarin (international normalized ratio [INR] 2.0 to 3.0) is highly effective in the reduction of ischemic stroke in patients with nonvalvular atrial fibrillation (AF). We hypothesized that the introduction of fixed low-dose warfarin alone or in combination with aspirin (300 mg) could normalize hemostatic markers, namely plasma fibrin D-dimer (an index of thrombogenesis), plasminogen activator inhibitor-1 (PAI-1, an index of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
55
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 19 publications
4
55
4
1
Order By: Relevance
“…Mean plasma D-dimer concentrations of untreated patients with chronic atrial fibrillation are higher than those of control individuals and decrease to concentrations similar to those of the controls on anticoagulation therapy (41,42 ). The D-dimer assay appears to retain utility in select patient groups, but the results need to be more carefully considered (43,44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mean plasma D-dimer concentrations of untreated patients with chronic atrial fibrillation are higher than those of control individuals and decrease to concentrations similar to those of the controls on anticoagulation therapy (41,42 ). The D-dimer assay appears to retain utility in select patient groups, but the results need to be more carefully considered (43,44 ).…”
Section: Discussionmentioning
confidence: 99%
“…21 Li-Saw-Hee et al and Jeffrey Liles et al confirmed the presence of higher levels of vWF in patients with AF compared to healthy controls. 22,23 Ammash et al demonstrated that elevated vWF:Ag may help identify patients with AF at risk of left atrial appendage thrombus. 24 Meanwhile, Roldán et al demonstrated that high plasma vWF levels are an independent risk factor for adverse events in anticoagulated patients with AF, 8 and Lind et al associated vWF factor with all-cause mortality and cardiovascular events in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…21,29 Plasma levels of vWF antigen are somewhat reduced by OAC treatment. 23,25 As it is well known, vWF possesses several functions in hemostasis; among them, some of the most important might be protecting factor VIII from proteolysis or cellular uptake besides binding to the surface of activated platelets and endothelial cells. 5 Thrombin cleaves vWF off of FVIII, releasing it to mediate platelet adhesion and aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected only once during OAC treatment and there are conflicting views regarding the possible effects of concomitant OAC treatment on VWF levels [28][29][30]. ABO blood group status is known to affect the levels of VWF [31,32], but such data were not available.…”
Section: Discussionmentioning
confidence: 99%